The Role of Gut Microbiota in Some Liver Diseases: From an Immunological Perspective - Wang, Li; Cao, Zheng-Min; Zhang, Li-Li; Li, Juan-mei; Lv, Wen-liang (Frontiers in Immunology, 2022)
Abstract：Gut microbiota is a microecosystem composed of various microorganisms. It plays an important role in human metabolism, and its metabolites affect different tissues and organs. Intestinal flora maintains the intestinal mucosal barrier and interacts with the immune system.Diet, drugs and other factors can upset the balance of gut bacteria, which can lead to various diseases. The liver is closely linked to the intestine by the gut-liver axis. As the first organ that comes into contact with blood from the intestine, the liver will be deeply influenced by the gut microbiota and its metabolites, and the intestinal leakage and the imbalance of the flora are the trigger of the pathological reaction of the liver. In this paper, we discuss the role of gut microbiota and its metabolites in the pathogenesis and development of autoimmune liver disease((including autoimmune hepatitis, primary biliary cirrhosis, primary sclerosing cholangitis), metabolic liver disease such as non-alcoholic fatty liver disease, cirrhosisits and its complications, and liver cancer from the perspective of immune mechanism. And the recent progress in the treatment of these diseases was reviewed from the perspective of gut microbiota.